2012
DOI: 10.2147/amep.s20219
|View full text |Cite
|
Sign up to set email alerts
|

Is video review of patient encounters an effective tool for medical student learning? A review of the literature

Abstract: PurposeTo determine if video review of student performance during patient encounters is an effective tool for medical student learning.MethodsMultiple bibliographic databases that include medical, general health care, education, psychology, and behavioral science literature were searched for the following terms: medical students, medical education, undergraduate medical education, education, self-assessment, self-evaluation, self-appraisal, feedback, videotape, video recording, televised, and DVD. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 86 publications
0
33
0
1
Order By: Relevance
“…Finally, because the video displays concrete and observable behaviors in a neutral way, it also avoids any source of misunderstanding between the student and the supervisor (9) and may stimulate the sharing of perceptions. This can be especially useful to teach dimensions such as communication and professionalism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, because the video displays concrete and observable behaviors in a neutral way, it also avoids any source of misunderstanding between the student and the supervisor (9) and may stimulate the sharing of perceptions. This can be especially useful to teach dimensions such as communication and professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…This is of importance since several studies have shown a decline in empathy among students and residents during undergraduate and graduate medical education (25). Self-reflection during review of student videos linked to supervisor or peer feedback seems to be an effective and valued way to learn communication and professional attitudes (26, 27) and is more beneficial than traditional feedback on students’ communication skills (9). Video-based stimulated recall has also been shown to be useful to stimulate clinical reasoning or to facilitate development of shared cognition (28, 29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have evaluated the utility of video recordings for subsequent evaluation and debriefing (811) and for improving self-assessment (1214), but the vast majority studied simulated surgical scenarios or physical examination skills rather than operative videos from patient procedures. Video-based coaching can be a useful tool for providing individualized, targeted feedback for trainees (15), and reinforces intraoperative teaching points (16) in a less stressful environment and has also been shown to improve skill acquisition (17).…”
Section: Introductionmentioning
confidence: 99%